BS EN IEC 61557-9. Electrical safety in low voltage distribution systems up to 1 000 V a.c. and 1 500 V d.c. Equipment for testing, measuring or monitoring of protective measures. Part 9. Equipment for insulation fault location in IT systems (7th May 2021) - British Standards Institution,
No abstract available